Innovation in small-scale aquaculture in Chile. Issue 2 (3rd April 2018) - Salazar, César; Jaime, Marcela; Figueroa, Yanina; Fuentes, Rodrigo
ABSTRACT: In light of the current depletion of extractive marine resources and the sustainability issues that have arisen in the aquaculture industry, the small-scale aquaculture sector has emerged as a viable and sustainable alternative for generating income. To integrate the small-scale aquaculture sector into the food value chain, understanding the decision-making process to innovate becomes essential. This paper explores the factors underlying both innovation choices and intensity among small-scale aquaculture producers by utilizing exclusive census data from the small-scale aquaculture sector in Chile. The results indicate that education, secure property rights, internet access, participation in organizations, commercialization methods, government instruments, understanding of credit, and social learning promote innovation decisions. We also find that largest producers innovate in more areas, suggesting a role of size for both technological and non-technological innovations.